?USE OF FILTER CAKE, AS A SUBSTITUTE FOR CEREALS IN POULTRY FEED (Biological Sciences - PJSIR, 1997)
Filter cake, a by-product of sugar cane industry, was tested for incorporating as a new energy source in poultry feed, in place of cereals. Sun dried filter cake was used progressively at 5, 10 & 15 % Cor replacing rice and formulating economical and efficient rations. Substitution of filter cake up to 27 % showed no abnormal mortality but the growth (weight gain) was reduced when filter cake was given more than 15 %. The weight gain (% of initial weight) with feed containing J 5 % filter cake was 278 % as compared to 258 % by feed containing zero percent filter cake. Feed conversion ratio was also better with feed containing filter cake. The conversion value of feed containing 15 % filter cake was 2.25 compared with value 2.79 of feed without filter cake.